The Gods we worship live next door - Realuyo, Bino A. (Anvil Publishing, Inc., 2008)
"In Realuyo's landscape of poetry, the ruins and the ruined of the Philippines gather to speak of "memories that arises from simple truths," and prove that what the punished body cannot endure, the soul will ultimately witness, illuminate, and redeem"--Publisher's description.